The Effect of Inflation Rate, Interest Rate and Unemployment Rate on The Economic Growth of Malaysia - Priscilla Dorothy anak Impin; Kok, Sook Ching (Penerbit UMS, 2021)
This study examines the effect of selected macroeconomics variables including inflation rate, interest rate and unemployment rate on the economic growth of Malaysia for the period of 2010 to 2018. To identify the effect of inflation, real interest rate, and unemployment on the gross domestic product (GDP), the long-run and short-run relationships between these variables are estimated. The Autoregressive Distributed Lag (ARDL) method is used for cointegration analysis. In the long run, the inflation rate has a positive impact on economic growth, meanwhile, the interest rate has a negative impact on economic growth. There is no evidence of a long-run relationship between the unemployment rate and economic growth. Based on the Toda-Yamamoto causality test, there is a uni-directional causal relationship from economic growth to the unemployment rate.